HIF-1α and SOX2 expression in cervical squamous cell carcinoma - Milenković, Svetlana V.; Terzić, Tatjana; Vraneš, Boris; Soldatović, Ivan (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Hypoxia is one of the major changes that occurs in the tumor microenvironment. It has been observed that there are pluripotent cancer cells in the cancer cell population that affect tumor growth and their resistance to therapy. The aim of this study was to examine the expression of hypoxia-inducible factor-1 alpha (HIF-1α), endogenous marker of hypoxia, and SOX2, marker of the pluripotent stem cells existing in the normal adult tissues, in the cervical squamous cell carcinoma (SCC). Methods. The study was conducted in 90 women with invasive cervical SCC, divided into two groups – 60 women in the Group A, with FIGO IB1 < 20 mm tumors (no metastases in the lymph nodes), and 30 women in the group B with tumors FIGO I–II (positive lymph nodes). The basic clinical parameters were determined by standard histopathological analysis, and the expression of HIF-1α and SOX2 by immunohistochemical examination. Results. There was a significant difference between the groups A and B, in the expression of HIF-1α (p = 0.024), but not in the expression of SOX2 (p = 0.566). Expression of HIF-1α was significantly higher in the group with lymph node metastases and invasion of lymphovascular spaces (p
Keywords: uterine cervical neoplasms; neoplasm staging; prognosis; hypoxia; biomarkers